The International and Political Journal: The Women’s Movement in the United States 1900-1920 AD: the Women’s Suffrage Movement as a Model - Alwan, Dr. Muhamad Kasim (The International and Political Journal, 2024)
The study deals with analyze the features of the women’s American suffrage movement as the large as feminist movement that produced feminist political thought and practiced political activity to treat the issue of political representation in the United States. The first part of the research focuses on the status of stagnation of the movement at the beginning of the twentieth century, the second part deals with the stage of building and organizing the suffrage movement, then we refer to the third part, which explains the impact of the United States’ entry into World War I on the women’s suffrage movement and the role of that in confirming and ratifying the Nineteenth Amendment.